2014
DOI: 10.4236/abb.2014.59091
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid Alleviates Aluminum Toxicity in Tomato Seedlings (Lycopersicum esculentum Mill.) through Activation of Antioxidant Defense System and Proline Biosynthesis

Abstract: The aim of this work was to evaluate the alleviating efficacy of salicylic acid (100, 250 and 500 μM) against the toxic effects of aluminum (Al) on two tomato cultivars (GOWRI and SIRI) differing in their sensitivity to Al stress. Al treatment (500 µM) caused 40% -80% drop in plant growth, relative water content (RWC) and cell viability and a reduction of 1 -2.5 fold and 0.5 -2 fold in glutathione and proline content respectively, when compared to their control plants grown in Al free medium. Al treatment also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 41 publications
3
11
0
Order By: Relevance
“…Al-toxicity can stimulate ROS production, thus causing peroxidation of proteins and membrane lipids in plant cells [ 10 , 11 , 12 , 13 ]. Both MDA (an indicator for lipid peroxidation) and electrolyte leakage (an indicator for cell membrane integrity) are often used to estimate the ROS-mediated damage to cell membranes and to evaluate plant Al-tolerance [ 12 ]. To explore the role of S in mediating Al-induced oxidative stress, we measured H 2 O 2 production, MDA, and total soluble protein levels and electrolyte leakage in roots and leaves ( Figure 4 B–E,G–J).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Al-toxicity can stimulate ROS production, thus causing peroxidation of proteins and membrane lipids in plant cells [ 10 , 11 , 12 , 13 ]. Both MDA (an indicator for lipid peroxidation) and electrolyte leakage (an indicator for cell membrane integrity) are often used to estimate the ROS-mediated damage to cell membranes and to evaluate plant Al-tolerance [ 12 ]. To explore the role of S in mediating Al-induced oxidative stress, we measured H 2 O 2 production, MDA, and total soluble protein levels and electrolyte leakage in roots and leaves ( Figure 4 B–E,G–J).…”
Section: Resultsmentioning
confidence: 99%
“…Al-toxicity can cause the accumulation of reactive oxygen species (ROS), thus leading to peroxidation of proteins and membrane lipids in plant cells. Lipid peroxidation may cause loss of plasma membrane integrity and electrolyte leakage [ 9 , 10 , 11 , 12 , 13 ]. Increasing evidence shows that antioxidant enzyme activities play a key role in plant Al-tolerance [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…SA suppressed the Al-induced enhancement in SOD, GPX, and APX activities but alleviated the Al-induced reduction in CAT activity in rice (Pandey et al, 2013 ). In tomato, SA significantly reversed the Al-induced changes in the activities of SOD, POD, and CAT (Surapu et al, 2014 ). These discrepancies may be caused by the different research methods, the time course of measurements and plant species.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that Arabidopsis NPR1 plays a role in SA-mediated antioxidant defense under Al stress (Guo et al, 2014 ; Zhang et al, 2014 ). The protective effects of exogenous SA on Al-toxicity by preventing Al-induced oxidative stress have been extensively described in various plant species, such as, tomato (Surapu et al, 2014 ), Coffea arabica (Mu-oz-Sanchez et al, 2013 ), Cassia tora (Yang et al, 2003 ), cauliflower (Sinha et al, 2015 ), barley (Song et al, 2011 ), wheat (Uysal et al, 2009 ), Matricaria chamomilla (Kováčik et al, 2012 ), and rice (Pandey et al, 2013 ). It was found that SA suppressed the Al-induced enhancement of superoxide dismutase (SOD), glutathione peroxidase (GPX) and ascorbate peroxidase (APX) activities and increased catalase (CAT) activity in rice plants exposed to Al stress (Pandey et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…SA alleviated Al toxicity by positive modulation of the citrate efflux in Cassia tora roots [ 194 ]. In addition, Al toxicity was alleviated in tomato [ 195 ], and soybean [ 191 ] by SA (<20 µM) through activation of the antioxidant system.…”
Section: Role Of Mineral Nutrition For Mitigating Aluminum Toxicitmentioning
confidence: 99%